2019
DOI: 10.1177/1591019919894800
|View full text |Cite
|
Sign up to set email alerts
|

ADAPT technique in ischemic stroke treatment of M2 middle cerebral artery occlusions in comparison to M1 occlusions: Post hoc analysis of the PROMISE study

Abstract: Background/purpose The benefit of endovascular thrombectomy in acute ischemic stroke (AIS) therapy of proximal large vessel occlusions (LVO) is established. However, there are few prospective studies evaluating the use of a direct aspiration first pass technique in distal vessel occlusions. This post hoc analysis of the PROMISE study examines the safety and effectiveness of the Penumbra System with the ACE68 and ACE64 Reperfusion Catheters for aspiration thrombectomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Trials and large studies enrolled few M2 occlusions, despite the fact that they comprise approximately 40% of patients with ischemic stroke and a visible Ischemic stroke occlusion on computed tomography angiography (CTA) and can lead to permanent disabilities. [11][12][13] This was understandable given the goal of trials at the time, but as stent-retrievers are now produced in smaller sizes and some aspiration catheters have been deployed for distal occlusions, the optimal technical approach for patients with M2 occlusion remains unclear and of increasing interest.…”
Section: Introductionmentioning
confidence: 99%
“…Trials and large studies enrolled few M2 occlusions, despite the fact that they comprise approximately 40% of patients with ischemic stroke and a visible Ischemic stroke occlusion on computed tomography angiography (CTA) and can lead to permanent disabilities. [11][12][13] This was understandable given the goal of trials at the time, but as stent-retrievers are now produced in smaller sizes and some aspiration catheters have been deployed for distal occlusions, the optimal technical approach for patients with M2 occlusion remains unclear and of increasing interest.…”
Section: Introductionmentioning
confidence: 99%
“…6 Navia et al found that good postprocedure reperfusion (an mTICI score of 2b/3) (93% vs. 92%, p ¼ 1.00), functional independence (57% vs. 70%, p ¼ 0.18), symptomatic intracranial hemorrhage (1.6% vs. 2.7%, p ¼ 0.55), device-or procedure-related serious adverse events at 30 days (4.0% vs. 8.1%, p ¼ 0.39), and mortality at 90 days (6.6% vs. 2.7%, p ¼ 0.69) were comparable between patients with M1 and M2 occlusions. 12 In the present study, we did not compare results of endovascular treatments for M1 and M2 occlusions.…”
Section: Discussionmentioning
confidence: 82%
“…Our results are also in this range (83%), comparable to those of a recent meta-analysis (81%) [ 23 ], and higher than in the Hermes registry (71%) [ 6 ]. As far as the available literature shows, the chance for successful recanalization is equal or even higher for M2 than for M1 occlusions [ 9 , 14 , 24 , 25 ]. Compared to the STRATIS-Registry, the overall results for good clinical outcome and mortality within the GSR are less favorable, especially when considering M1 occlusions [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, vascular injury may be more common in smaller diameter vessels with conventional stent retrievers, and as a result, the rate of hemorrhagic complications may be higher in M2 rather than in M1 occlusions [ 9 , 11 , 12 , 13 ]. Furthermore, not all M2 occlusions are accessible using distal aspiration catheters, potentially making direct contact aspiration or a combined technique such as SAVE (stent retriever assisted vacuum-locked extraction) impossible [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%